TANTANGAN DAN SOLUSI APLIKASI TELEVISI WHITE SPACE DI INDONESIA - Kiki Prawiroredjo; Tjandra Susila (Jetri : Jurnal Ilmiah Teknik Elektro, 2014)
Television White Space (TVWS) are television channels that are not used by any licensed services in a particular location and a particular time. To improve the efficiency of the TVWS spectrum, regulators have begun to develop regulations to allow the use of TVWS by unlicensed wireless devices as long as they do not interfere with any licensed service. This article describes TVWS regulatory status in the US and Europe, analyzes the problems and explains the coexistence in TVWS coexistence mechanisms that exist to improve the TVWS coexistence as the input to the government and TVWS users in Indonesia in the future. In metro areas in Indonesia TVWS can solve the lack of frequency spectrum for wireless communication network such as Wi-Fi or smart phone. In underdeveloped area in Indonesia, TVWS system is needed to develop an internet or to monitor catastrophic events as an early warning system. Keywords: TVWS, spectrum, coexistence, wirelessTelevisi White Space (TVWS) adalah kanal televisi yang sedang tidak digunakan oleh pemancar yang berlisensi pada tempat dan waktu tertentu. Untuk meningkatkan efisiensi spektrum TVWS, para regulator dunia mulai mengijinkan penggunaan TVWS oleh peralatan nirkabel yang tidak berlisensi selama mereka tidak mengganggu pemancar yang berlisensi. Pada artikel ini dijelaskan status regulasi TVWS di Amerika dan Eropa, masalah-masalah koeksistensi pada TVWS dan mekanisme untuk memperbaiki koeksistensi pada TVWS yang diharapkan dapat menjadi masukan bagi pemerintah maupun pengguna TVWS di Indonesia dimasa depan. Di daerah perkotaan di Indonesia TVWS diperlukan untuk memecahkan masalah kekurangan spektrum frekuensi dengan berkembangnya pengguna jaringan komunikasi nirkabel seperti wi-fi maupun telepon pintar. Sistem TVWS diperlukan untuk membangun jaringan internet atau memantau bencana alam sebagai sistem peringatan dini di daerah yang belum berkembang di Indonesia